Minimizing the Number of Label Transitions Around a Nonseparating Vertex of a Planar Graph - Mohar, Bojan; Škoda, Petr (Journal of Graph Algorithms and Applications, 2012)
We study the minimum number of label transitions around a given vertex v0 in a planar multigraph G,in which the edges incident with v0 are labelled with integers 1, …, l, and the minimum is taken over all embeddings of G in the plane.For a fixed number of labels, a linear-time fixed-parameter tractable algorithm that computes the minimum number of label transitionsaround v0 is presented.If the number of labels is unconstrained, thenthe problem of deciding whether the minimum number of label transitions is at most kis NP-complete. <!---->